The Younger Bronze Age and the Beginning of the Iron Age in Chełmno Land in the Light of the Evaluation of Selected Finds of Metal Products - Gackowski, Jacek (Analecta Archaeologica Ressoviensia, 2017)
The article presents selected finds, both previously discovered and recent ones made of metal (bronze and iron), originating from Chełmno land and related with the settlement of the Lusatian population in the Younger Bronze Age and at the beginning of the Iron Age. Due to the discovery of several casting workshops and other traces of local bronze production, it is possible to assume that a certain selection of ornaments, weapons and tools was produced locally. However, the stylistic and utility models were always of supra-regional origin, for which many analogies can be found in the area of Kuyavia, Greater Poland and Silesia. Similar provenance has been noticed for iron objects discussed in the research.